Deactivation of Industrial Pd/Al2O3 Catalysts by Ethanol: A Spectroscopic Study. Issue 3 (10th December 2020) - Carosso, Michele; Vottero, Eleonora; Morandi, Sara; Manzoli, Maela; Ferri, Davide; Fovanna, Thibault; Pellegrini, Riccardo; Piovano, Andrea; Groppo, Elena
Abstract: The chemical processes involved in the decomposition of ethanol over two industrial Pd/Al2 O3 catalysts characterized by different Pd dispersions, particles morphology and reducibility of the active metal phase was thoroughly investigated in gas‐phase and in liquid‐phase by transmission FT‐IR and ATR‐IR spectroscopies, respectively. In both cases, two main products were detected, arising from two competitive paths: acetates from ethanol oxidation and carbonyls from acetaldehyde decarbonylation. The regularity of the Pd particles greatly affects the relative proportion of the two products, while the initial Pd oxidation state influences the kinetics of the two processes. Ethanol oxidation to acetates is the kinetically favored reaction path both in gas‐phase and in liquid‐phase. In contrast, the presence of a solvent dampens the decarbonylation process to very low levels, because the solvent competes with ethanol in occupying the available surface sites. Since adsorbed carbonyls are considered as surface poisons of industrial Pd/Al2 O3 catalysts in processes involving aliphatic as well as aromatic alcohols, the rationalization of the experimental variables affecting alcohols decomposition can help in establishing working protocols and in designing preparation procedures that minimize the unwanted poisoning effects. Abstract : Take a closer look : The interaction of gaseous as well as liquid ethanol over Pd/Al2 O3 catalysts was studied by FT‐IR and ATR‐IR spectroscopies, respectively. We identified acetates and carbonyls as decomposition products and potential surface poisoning. Particular care is devoted to the rationalization of the catalyst properties affecting such phenomenon. This would allow for the design of systems able to minimize the unwanted poisoning.